Propaganda and counter-propaganda in the official press during the Spanish Transition (1975-1978). Arriba vs. Odiel - Martínez Fábregas, Jezabel (Ámbitos. Revista Internacional de Comunicación, 2019)
This manuscript aims at unveiling whether the newspapers Arriba and Odiel went on being propaganda organs during the Spanish Transition, or if they assumed their role as political agents. To carry out this research, we have applied content analysis to opinion texts published in them since Franco’s demise (November 1975) up to the referendum on the Constitution (December 1978). This study provides evidence of that Odiel, being one of the smallest dailies within the Movement Press’ chain, did not follow the dictations coming from the national reference newspaper, Arriba, and, accordingly, shows the lack of a homogeneous discourse.